The Education of Children in the Family from the Perspective of Hadith - Muhammad Zainul Husna; Salwa Ghina Osiska; Amriatul, Mansur (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
Abstrak ; This article examines the role of parents in children’s education based on prophetic traditions (hadith tarbawi), emphasizing responsibility, exemplary behavior, and compassion within the family environment. Families function as the earliest and primary educational setting that shapes children’s moral, spiritual, and social foundations. Using a qualitative literature study approach, this study analyzes relevant hadiths, classical Islamic sources, and contemporary Indonesian research. The findings reveal that the Prophet Muhammad provided a comprehensive framework for child education rooted in moral responsibility, exemplary conduct, and affectionate parenting. These values remain highly relevant for modern Muslim families in navigating digital challenges and maintaining healthy parent–child relationships. The study concludes that hadith-based education strengthens family resilience and contributes to forming a pious, ethical, and emotionally balanced generation.